DANAU TIRTA GANGGA MEMBANGUN PERILAKU SOSIAL DAN KESADARAN EKOLOGIS UMAT HINDU DI KAMPUNG SWASTIKA BUANA KECAMATAN SEPUTIH BANYAK - Anisa Dwi Rahayu; Muslimin Muslimin; Luthfi Salim; Siti Badi’ah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The relationship between religion, local wisdom, and environmental sustainability is an important issue in the sociology of religion, particularly among communities that continue to uphold traditional values in their interaction with nature. Tirta Gangga Lake, as a sacred space for the Hindu community in Kampung Swastika Buana, represents how the religious values of Tri Hita Karana shape local patterns of social behavior and ecological awareness. This study aims to examine the role of Tirta Gangga Lake in shaping social behavior and ecological awareness among the Hindu community in Kampung Swastika Buana, Seputih Banyak District, Central Lampung. Using a qualitative approach with case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that Tirta Gangga Lake serves multiple functions: as a water source, center for religious activities, social interaction space, and medium for fostering ecological awareness based on Tri Hita Karana values. Analysis using Max Weber's social action theory reveals that community behavior encompasses traditional, value-rational, instrumental-rational, and affectual actions. The lake's sacredness significantly strengthens social solidarity, cooperation, and environmental responsibility.